PENERAPAN STRATEGI KOMUNIKASI PEMASARAN MELALUI CUSTOMER RELATIONSHIP MANAGEMENT DI HERCO DIGITAL INDONESIA - ISTIGHFAROH, DINI (JIKE : Jurnal Ilmu Komunikasi Efek, 2023)
In a company, customer loyalty has an important role. Business competition is getting tougher between institutions as a result of customers who are getting smarter, more price-conscious, and more approachable by products. As a result, a marketing communication strategy that focuses on efforts to maintain customer relationships is required. Customer Relationship Management is a marketing communication strategy that focuses on efforts to maintain customer relationships. To maintain customer relationships and meet customer needs, Herco Digital Indonesia employs a Customer Relationship Management strategy. The purpose of this research is to discover and explain how the implementation of Customer Relationship Management is carried out by Herco Digital Indonesia to create customer loyalty. This research uses a descriptive qualitative research method. This study was conducted at Herco Digital Indonesia, which is located at Ruko Mataram Plaza, Jl. MT. Haryono No. 427-429, Jagalan, Semarang City. Interviews, observation, and documentation were used to collect data. The data analysis used is a descriptive analysis in which the application of Customer Relationship Management is explained and described, and conclusions are drawn from the analysis. The findings of this study demonstrate how Herco Digital Indonesia implements a Customer Relationship Management strategy by utilizing Customer Relationship Management workings and the Customer Relationship Management process. Several points, however, have not been maximized in its implementation; these are the processes of collecting customer data and customer identification; discovering information about what customers want from the company; and developing and implementing the Customer Relationship Management program. Keywords: Customer Relationship Management; Customer loyalty; Marketing Communication